1994
DOI: 10.1017/s0001924000026786
|View full text |Cite
|
Sign up to set email alerts
|

A dual-time method for the solution of the unsteady Euler equations

Abstract: A “dual-time” method for solving the three-dimensional Euler equations describing the compressible flow about wings undergoing arbitrary motions and deformations is presented. A finite-volume formulation is chosen where the volumes distort as the wing moves or deforms. Independent motion of the inner and outer boundaries of the grid is permitted with a sequence of grids generated using transfinite interpolation. An implicit real-time discretisation is used, and the equations are integrated in a fic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 3 publications
1
38
0
Order By: Relevance
“…The difference becomes most marked at the larger angles of incidence when the shock wave is present. The moment location which consistently gives closer comparison between inviscid computations and measured values is 0.273c [2,4,15,16]. However, for the current turbulent results, it was found that using the quoted experimental moment centre at 0.25c gives close agreement with experimental measurements.…”
Section: Test Casessupporting
confidence: 57%
“…The difference becomes most marked at the larger angles of incidence when the shock wave is present. The moment location which consistently gives closer comparison between inviscid computations and measured values is 0.273c [2,4,15,16]. However, for the current turbulent results, it was found that using the quoted experimental moment centre at 0.25c gives close agreement with experimental measurements.…”
Section: Test Casessupporting
confidence: 57%
“…Using a dual time-stepping method [62], backward differences are implicitly being used for the time derivatives. This means that the solution at each time level depends only upon the solution calculated at previous time levels.…”
Section: Flux-splittingmentioning
confidence: 99%
“…For time integration of equations used an implicit dual time method (Jameson 1991;Gaitonde 1994;Jahangirian and Hadidoolabi 2004), in real time a second order accurate backward difference formula (BDF) is used as follows…”
Section: Solution Algorithmmentioning
confidence: 99%
“…For time integration of equations used an implicit dual time method (Jameson 1991;Gaitonde 1994;Jahangirian and Hadidoolabi 2004). Considering the fixedness of the volume of elements in rotational motions of the body in the introduced grid, there is no need to calculate elements volume in every time step therefore the calculations decreases.…”
Section: Introductionmentioning
confidence: 99%